PERANCANGAN SISTEM INFORMASI PENGOLAHAN DATA PASIEN PADA KLINIK POLI GIGI PUSDIKLAT MANAJEMEN PERTAHANAN: Information Systems;Dental Poli;Waterfall. - Nasrudin, Nasrudin; Suryani, Nining; Cahya Putri Buani, Duwi (JURNAL AKADEMIKA, 2021)
The Defense Management Training Center for Dental Polyclinic is one of the health service pro-viders at a Defense office, which is located at Jalan Jati No.1 Pondok Labu, South Jakarta. With a computerized system, it can be an alternative solution to medical record problems at the Dental Center for Defense Management Education and Training Clinic. The methods that the authors use in building a medical record information system design include observation methods, interviews, literature studies, waterfalls, blackbox testing, system design, programming, program implemen-tation and database design making using ERD and LRS. This program will be built using the Java programming language with the Netbeans 8.2 application. Hopefully the design of a patient data processing information system at the Defense Management Education and Training Center dental clinic can help the process of running medical record activities in the dental poly clinic of the De-fense Management Training Center.